2008
DOI: 10.1111/j.1752-7325.2007.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental Fluorosis in 12‐ and 15‐Year‐Olds at High Altitudes in Above‐Optimal Fluoridated Communities in Mexico

Abstract: At least 8 out of 10 adolescents had some level of fluorosis, and such prevalence is considered to be a dental public health problem. A relationship between fluoride concentration in water in each community and fluorosis was observed. The high fluorosis prevalence and severity might possibly be associated with the high altitude of the communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 5 publications
1
22
0
6
Order By: Relevance
“…13 In Brazil, similar tendencies exist, showing an increase of 230% from 2003 to 2010. 32 Prevalence in zones where fluoride in water was optimal or below (<1.5ppmF) ranges between 15.5 to 89.8%, the highest (>80%) were reported in Hidalgo, 29 Oaxaca 27 and Morelos. 22 In these two last states mentioned fluoridated salt distribution is allowed, 33 this should be revised and adjustments performed to avoid an extra source of fluoride in these populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 In Brazil, similar tendencies exist, showing an increase of 230% from 2003 to 2010. 32 Prevalence in zones where fluoride in water was optimal or below (<1.5ppmF) ranges between 15.5 to 89.8%, the highest (>80%) were reported in Hidalgo, 29 Oaxaca 27 and Morelos. 22 In these two last states mentioned fluoridated salt distribution is allowed, 33 this should be revised and adjustments performed to avoid an extra source of fluoride in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate and severe DF was associated with soft drink consumption (table II). 29 reported an overall fluorosis prevalence of 83.8% in three communities in the State of Hidalgo, located >2 000m amsl. Prevalence found in each community was 89.8 (1.38 ppmF), 81.9 (1.42 ppmF) and 94.7 (3.07 ppmF).…”
Section: Studies In Communities Where Water Fluoride Content Is Abovementioning
confidence: 99%
See 1 more Smart Citation
“…Several Mexican communities have reported that fluoride concentrations in drinking water are higher than optimal [Pontigo-Loyola et al, 2008], and, therefore, five states of the country [NOM, 1995] are excluded from the salt fluoridation program. The state studied herein, Morelos, is not among these five states, so its population receives fluoridated and iodized salt.…”
Section: Dental Fluorosismentioning
confidence: 99%
“…Many strategies for establishing respectful collaborations are rooted in community-based participatory research practices including development of community-representative boards to highlight issues of concern regarding the project, and employment of a facilitator to ensure productive communication between community and research partners. The consultation element is especially crucial when groups possess defined political or review processes such as tribal entities, and negotiations may require a shift of traditional research control to the community in exchange for their approval and support of the partnership [32,35,36,37]. Some have suggested creating tangible benefits for community endorsement and collaboration including compensation in the form of resources for health care infrastructure, reimbursement of costs, or even revenues from for-profit ventures or industry-driven research [38].…”
Section: Cgn Strategies That Influence Minority Participation In Biommentioning
confidence: 99%